Optimization Modeling of a Poultry Industry Supply Chain Network - Mohammad Khadem; Ahm Shamsuzzoha; Sujan Piya (International Journal of Supply Chain Management, 2017)
Supply chain management is an asset to every industry globally due to its positive outcomes such as faster response time, reduction of unwanted inventory and lower sales costs with enhanced customer service. It is therefore important to focus on improving the supply chain network of any industry. The objective of this research study is to model a supply chain network for poultry Industry in Oman. The study analyzes the existing supply chain network within a poultry industry and recommended its improvement based on the identified factors while giving more emphasis on the routing and distribution network aspects of supply chain. The recommendation, in the form of optimization model, is verified and validated using Lingo optimization software. Also, heuristic method is proposed and tested to overcome the complexity of optimization model.